Critical review of evidence for the role of physical activity in the management of type 2 diabetes and physical activity in patients with diabetes in the state of Qatar - Sheik, Sanaulla (International Journal Of Community Medicine And Public Health, 2023)
Globally prevalence of diabetes is increasing. Sedentary lifestyle and lack of physical activity is strongly associated with its prevalence and complications from the disease. This is also reflected in the people living in Qatar. Attempt to critically review the evidence on the effect of physical activity on diabetes and also review on the evidence available about the perception of people about physical activity in the state of Qatar. Critical appraisal of PubMed and google scholar using PICO model to gather the evidence available, including search of worldwide web for the terms ‘physical activity’, ‘diabetes mellitus type 2’. The results were critically appraised and presented in this review. Qatar has strong infrastructure of healthcare to support the people suffering from diabetes with its stable primary care, advanced secondary care and facilities. The municipalities have provided good green zones for the people to carry on the physical activity. The weather is not favorable throughout the year due to extremely hot summers but there are facilities which continue to function providing opportunities for physical activity. With the continued efforts of the governmental bodies increasing awareness, the perception of people is positive towards physical activity.